Body composition and socioeconomic factors in patients with hepatic steatosis - Josilda Ferreira Cruz; Ariel Figueiredo Oliveira; Demetrius Silva de Santana; Sonia Oliveira Lima; Mário Augusto Ferreira Cruz; Marcelo Augusto Ferreira Cruz (Universidade Estadual de Maringá, 2017)
The study aimed to evaluate the association of the components of body composition (body mass index - BMI, waist circumference, basal metabolism, body fat percentage, fat weight, fat free percentage and lean weight) with gender, age, income and schooling in patients with hepatic steatosis. Descriptive and survey study, with quantitative analytical approach. Data were collected through ultrasound and bioimpedance tests. The significance was p < 0.05 and software used was SPSS 22.0. A sample of 114 patients with hepatic steatosis, 70.1% were women. The mean age was 46.2, only 11.4% had normal BMI. The mean BMI was 30.4, waist circumference 100.2 cm, fat percentage 37.97%, basal metabolism 1451.9 kcal, fat weight 31.0 kg. Statistical differences in several variables in relation to gender and age were found. However, no statistically significant differences were found regarding schooling and income. Changes in body composition were obvious in patients with hepatic steatosis.